Properties of Arboreal Ant and Ground-Termite Nests in relation to Their Nesting Sites and Location in a Tropical-Derived Savanna - B. C. Echezona; C. A. Igwe; L. A. Attama (Psyche: A Journal of Entomology)
Ecosystem engineers such as ants and termites play an important role in the fertility of tropical soils. Physicochemical analyses were thus carried out on some arboreal ant nests collected from mango (Mangifera indica), bush mango (Irvingia gabonensis), kola (Cola nitida), newbouldia plant (Newbouldia laevis), and oil bean plant (Pentaclethra macrophylla) and on ground nest of termite, Odontotermes sudanensis Sjost. (Isoptera: Termitidae) in Nigeria. Arboreal nests, particularly those of M. indica, were significantly richer in the chemical constituents sampled, compared to those of ground-termite nests or adjacent unaffected soils. Available water capacity of nests from M. indica (60.0%) was significantly higher than those of other sites or locations sampled. While biogenic structures were sandy-loamy in texture, their corresponding adjacent soils were either sandy or sandy-loamy. Soils worked by ants and termites had greater proportions of silt-sized (17.9 versus 9.7) and clay-sized (19.2 versus 9.3) to the detriment of coarse-sized particles (51.2 versus 60.9) and fine-sand-sized particles (11.7 versus 20.1) relative to the adjacent soils. Generally, biogenic structures were about 348% richer in P than their corresponding adjacent soils; an attribute, which holds a strong promise in bioremediation and biofortification of soils especially during amendment.